Fenomena Pump and Dump dalam Transaksi Saham: Perspektif Hukum Positif dan Hukum Islam - Dearty Tri Adilla; Ahmad Misbakh Zainul Musthofa; Anggi Irawan (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the phenomenon of pump and dump in stock trading from the perspective of positive law in Indonesia as well as Islamic law, in order to determine the extent of legal protection provided to investors who fall victim to market manipulation. The method used is qualitative research with a normative juridical approach, presented comparatively between the provisions of Law Number 8 of 1995 concerning Capital Markets, Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK), and the principles of Islamic economic law. The findings indicate that pump and dump practices constitute a form of market manipulation that violates the principles of transparency and fairness under positive law and contradicts the Islamic values of honesty (shidq), justice (‘adl), and the prohibition of deception (gharar and tadlis). Law enforcement against perpetrators still faces technical challenges and issues related to digital evidence, thus strengthening regulation and market education based on Islamic ethics is deemed necessary.